Interaction Analysis of Adenovirus L5 Protein With Pancreatic Cancer Cell Surface Receptor to Analyze Its Affinity for Oncolytic Virus Therapy - Nisar, Maryum; Paracha, Rehan Zafar; Gul, Alvina; Arshad, Iqra; Ejaz, Saima; Murad, Didar; Khan, Shahzeb; Mustansar, Zartasha (Frontiers in Oncology, 2022)
This study seeks to investigate the interaction profile of L5 protein of oncolytic adenovirus with the overexpressed surface receptors of pancreatic cancer. This is an important area of research because pancreatic cancer is one of the most fatal malignancies with a very low patient survival rate. Multiple therapies to-date to improve the survival rate are reported however, they show a comparatively low success rate. Amongst them, oncolytic virus therapy is a type of immunotherapy which is currently under deliberation by the researchers for multiple cancer types in various clinical trials. T-VEC is the first oncolytic virus approved by Food and Drug Administration (FDA) U.S for melanoma. The oncolytic virus not only kills cancer cells but also activates anti-cancer immune response. Therefore, it is preferred over others to deal with aggressive pancreatic cancer. The efficacy of therapy primarily depends on how effectively the oncolytic virus enters and infects the cancer cell. Cell surface receptors and their interactions with virus coat proteins is a crucial step for oncolytic viruses entry and a pivotal determinant. The L5 proteins of virus coat are the first to interact with host cell surface receptors. Therefore, the objective of this study is to analyze the interaction profile of L5 protein of oncolytic adenovirus with overexpressed surface receptors of pancreatic cancer. The L5 proteins of three adenovirus serotypes HAdV2, HAdV5, and HAdV3 were utilized in this study. Overexpressed pancreatic cancer receptors include SLC2A1, MET, IL1RAP, NPR3, GABRP, SLC6A6, and TMPRSS4. Protein structures of viral and cancer cell protein were docked using the HADDOCK server. Binding affinity and interaction profile of viral proteins against all the receptors were analyzed. Results suggest that HADV3 L5 protein shows better interaction compared to HAdV2 and HAdV5 by elucidating high binding affinity with 4 receptors (NPR3, GABRP, SLC6A6, and TMPRSS4). The current study proposed that HAdV5 or HAdV2 virus pseudotyped with the L5 protein of HAdV3 can be able to effectively infect pancreatic cancer cells. Moreover, the current study surmises that the affinity maturation of HAdV3 L5 can enhance virus attachment with all the receptors of cancer cells.